A combined treatment approach for dye and sulfate rich textile nanofiltration membrane concentrate. (December 2019) - Balcik-Canbolat, Cigdem; Olmez-Hanci, Tugba; Sengezer, Cisel; Sakar, Hacer; Karagunduz, Ahmet; Keskinler, Bulent
Abstract: Fenton process and Fenton coupled biological treatment were examined for the treatment of the textile nanofiltration (NF) membrane concentrate. Maximum chemical oxygen demand (COD) and total organic carbon (TOC) removal efficiency was found to be 87.1% and 80.8% respectively at molar concentrations of 35 mM Fe 2+ and 175 mM H2 O2 and pH 3 for 30 min in the single Fenton process. As a second alternative, sequencing batch reactor (SBR) was operated to carry out biological treatment after Fenton process at a lower chemical dosage (pH: 3, CFe+2 : 20 mM, CH2O2 : 100 mM, 30 min). The ratio of biological oxygen demand in 5 days (BOD5 )/COD was enhanced to 0.51 at molar concentrations of 20 mM Fe 2+ and 100 mM H2 O2 . According to respirometric analysis and SBR results, it was stated that the oxidation intermediates formed during the treatment of membrane concentrate with Fenton process had no inhibitory/toxic effects on the hetetrophic biomass. The maximum COD removal efficiency in biological treatment after Fenton process was 75% under equilibrium condition using a SBR operated at 10 days of sludge retention time and 12 h of hydraulic retention time (HRT).